Polymeric Nanocarrier system Bearing Anticancer Agent for the Treatment of Prostate Cancer: Systematic Development and in vitro Characterization - Panda, Pritish Kumar; Jain, Sanjay K. (International Journal of Pharmaceutical Investigation)
Objectives: Doxorubicin-bearing polymeric (PLGA) nanoparticles (PNPs) were prepared for the treatment of prostate cancer. Materials and Methods: These PNPs were prepared using the solvent evaporation method and characterized using UV, NMR, Particle size Analyser, SEM, and TEM for the determination of shape, size, zeta potential, and polydispersity index. Moreover, in vitro drug release, SRB assay, apoptosis, and haemolytic study were also performed to prove its potentiality for prostate cancer. Results: The mean particle size (MPS), polydispersity index (PDI), and zeta potential (ZP) of PNPs were found to be 101.3 ± 1.23 nm, 0.240 ± 0.28 and -3.11 ± 1.96 mV, respectively. SEM and TEM revealed that the PNPs are spherical in shape and the sizes are approximately 100 nm. The entrapment efficiency, loading efficiency, and percentage drug release of doxorubicin from PNPs were found to be 69.38 ± 1.76%, 4.2 ± 0.64% and 77.56 ± 4.24%, respectively. In addition, cellular apoptosis against PC-3 cell lines was found to be ≥ 5.15 fold and haemolysis toxicity was reduced to ≤ 3.5 fold with PNPs as compared to free drug. Conclusion: These findings demonstrated that PNPs have the potential to deliver the anticancer agent to tumor sites and could be an emerging strategy for the treatment of prostate cancer.
Keywords: Polymeric nanoparticles; Targeting; Doxorubicin; PLGA; Prostate cancer.